Disseminated Intravascular Coagulation and Hemorrhage After Dilation and Evacuation Abortion for Fetal Death. Issue 2 (June 2020) - Kerns, J.L.; Ti, A.; Aksel, S.; Lederle, L.; Sokoloff, A; Steinauer, J.
Abstract : ( Obstet Gynecol . 2019;134:708–713) Second-trimester surgical abortion, or dilation and evacuation (D&E) complications are rare. At a mere 0.7% to 3%, these complications can include cervical laceration, uterine perforation, infection, and hemorrhage [including hemorrhage related to disseminated intravascular coagulation (DIC)]. The possibility of excessive blood loss associated with DIC can even lead to the need for transfusion, or in extreme cases, maternal death. A dearth of well-controlled, large sample size studies evaluating the association of fetal death and abortion-related hemorrhage or DIC makes it difficult to create guidelines for appropriate preoperative preparation and anticipation of needed interventions. This study aimed to determine postabortion risk of hemorrhage for patients with a second trimester fetal death. It sources data from a large cohort at a public, urban abortion clinic.